The Quality of Yellow Fin Tuna Powder (Thunnus Albacores) as a Natural Flavoring Alternative (International Journal of Scientific Research and Management (IJSRM), 2021)
Flavoring is already commonly used by the community, but on the market, flavoring generally contains monosodium glutamate (MSG). Alternative processed yellow fin tuna (Thunnus albacores) into natural flavoring fish powder without MSG becomes interesting and very useful for reducing MSG intake in the people of North Maluku. This type of research is experimental research conducted in September - November 2018 in the SIG Laboratory, Bogor for chemical quality testing (sodium, water, protein, and total fat) and Food Organizing Laboratory for Nutrition Department of Health Ministry of Ternate for making fish powder and organoleptic quality tests (color, texture, aroma, and taste). Chemical test results obtained sodium content of 3204.79 mg / 100 g of sample, moisture content of 6.08%, protein of 48.76%, and total fat of 3.28%; and the organoleptic test results obtained a mean ± SD of the color aspect of 4.0 ± 0.7, texture of 3.5 ± 0.9, aroma of 4.1 ± 0.8, and taste of 3.7 ± 1, 0. It was concluded that the heating process (roasted and oven-dried) affected the chemical quality of yellow fin tuna powder, and obtained sodium 3204.79 mg / 100 g, Water content 6.08%, protein content 48.76%, and total fat 3.28%; and in terms of organoleptics, the average panelist likes color and aroma, while aspects of taste and texture are only part of the panelists who say they like.